The Role of the Human Hypothalamus in Food Intake Networks: An MRI Perspective - Roger, Coleen; Lasbleiz, Adèle; Guye, Maxime; Dutour, Anne; Gaborit, Bénédicte; Ranjeva, Jean-Philippe (Frontiers in Nutrition, 2022)
Hypothalamus (HT), this small structure often perceived through the prism of neuroimaging as morphologically and functionally homogeneous, plays a key role in the primitive act of feeding. The current paper aims at reviewing the contribution of magnetic resonance imaging (MRI) in the study of the role of the HT in food intake regulation. It focuses on the different MRI techniques that have been used to describe structurally and functionally the Human HT. The latest advances in HT parcellation as well as perspectives in this field are presented. The value of MRI in the study of eating disorders such as anorexia nervosa (AN) and obesity are also highlighted.